On algebras of the Temperley-Lieb type associated with algebras generated by generators with given spectrum - Zavodovskii, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We introduce and study algebras of the Temperley-Lieb type associated with algebras generated by linearly connected generators with given spectrum. We study their representations and the sets of parameters for which representations of these algebras exist.